The Influence of Habitat and Arthropods on Insectivorous Birds and Bats in Western Sarawak, Borneo - Vivian, Soon (Universiti Malaysia Sarawak, 2024)
Natural predation by insectivorous birds and bats has high potential to offer a sustainable solution to pest management in the oil palm plantations. This study aimed to determine the species assemblage, abundance, species richness and activity patterns of insectivorous birds and bats in oil palm plantations (OP) and adjacent forest (SF) in Bau-Lundu region of western Sarawak. The study also assessed the relationship between the abundances of insectivorous predators and arthropods, and influence of various environmental variables (i.e. distance from forest, tree height, temperature, etc.) on their abundances. Bird surveys using point count method observed 318 individuals from 35 species from 18 families, where Rufous-tailed Tailorbird (31.8%) was the most abundant. Acoustic surveys of insectivorous bats recorded 5,299 echolocation calls from 23 species from 6 families, with Verpertilionids being the majority (69.8%) and Glischropus tylopus was the most abundant. Sticky traps and pitfall traps collected 8,544 arthropods from 20 orders, while vehicle-mounted tow net captured 42,170 arthropods from 15 orders. The most abundant arthropod order was Diptera (74.8%). Overall, the insectivorous predator and arthropod assemblages have significantly lower abundance and species richness in OP than in SF. The findings of this study do not generally support the hypothesis that higher predator abundance and species richness will result in lower prey abundance. While high bats abundance was reflected by the increase in arthropod abundance in OP, bird-arthropod relationship varied. Insectivorous bird abundance and species richness were negatively affected by distance from forest, but positively influenced by tree height. Insectivorous bats abundance was positively influenced by temperature and wind speed.